Changing trends in pediatric renal biopsies: analysis of pediatric renal biopsies in national nephrology registry data. (13th September 2016) - Fidan, Kibriya; Isik Gonul, Ipek; Büyükkaragöz, Bahar; Isiyel, Emel; Arinsoy, Turgay; Soylemezoglu, Oguz
Abstract: Renal biopsy is the gold standard method for determining the diagnosis, treatment, and prognosis in children with renal disease. This study aims to evaluate the histopathological features of pediatric renal biopsies obtained from the national nephrology registry in the last two decades. Data recorded in the Turkish Society of Nephrology Registry System (TSNRS) in 1991 as well as in between 2001 and 2010 were analyzed. A total of 3892 biopsies were recorded; with the least number in 1991 (total 103 biopsies from 17 centers) and the highest number in 2008 (total 654 biopsies from 23 centers). Glomerular diseases constituted the main group in the registry (62.64%), followed by systemic diseases (20.06%). Focal and segmental glomerulosclerosis (FSGS) and Henoch–Schönlein purpura (HSP) nephritis (IgA vasculitis) were the most common glomerular and systemic diseases, respectively. Overall prevalence of renal amyloidosis and membranous nephropathy (MN) was quite low (1.87% and 1.56%, respectively) in all periods. Compared to 1991, there was an increasing trend in the frequencies of certain disorders including hemolytic uremic syndrome (HUS), IgA nephropathy, and HSP nephritis; and there was a decrease in acute proliferative glomerulonephritis (GN) in 2008. As well as demonstrating the etiologies of renal diseases which can only be identified by renal biopsies, this study provides important information regarding the changing patterns of histopathological findings due to better management of pediatric renal diseases over the years in Turkey.